Pendekatan Psikologi dalam Membangun Komusnikasi Efektif pada Manajemen Organisasi - Alin Nur Indahsari; Nadia Yolanda Salsabila; Maftuhatul Afrah; Muallimin Muallimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Effective communication is a crucial element in the success of organizational management. In modern organizational practices, communication is not only concerned with the transmission of information but also involves psychological aspects such as perception, emotions, motivation, and interpersonal relationships among organizational members. This study aims to examine the role of psychological approaches in building effective communication within organizational management through a literature review method. The research data were obtained from scientific articles published between 2020 and 2025, accessed through Google Scholar and the Publish or Perish application. The initial search identified 30 articles; after the screening and eligibility processes, 27 relevant articles were selected. Further selection resulted in 5 articles that were most relevant to the research topic and were analyzed in depth. The findings indicate that psychological approaches such as emotional intelligence, empathy, motivation, and interpersonal perception play a significant role in enhancing the effectiveness of organizational communication. These findings suggest that integrating psychological approaches into organizational communication practices can improve the quality of workplace relationships, reduce conflicts, and enhance overall organizational performance.